The Effects Of Combination Of Behavioural Intervention, Nutritional Education And Exercise (Combine) Program On Haemostatic Markers Among Obese Subjects - Omar, Norsuhana (2012)
Obesity is a condition of excess body fat and it significantly increases the risk of coronary heart disease. Studies have shown that impaired haemostatic in obesity were found to predict future development of coronary heart disease and numbers of coronary events. The purpose of this study was to determine the effects of COMBINE program on the changes of anthropometry parameters, biochemical profile and haemostatic markers in obese subjects. The assessment was carried out on 28 obese subjects for 12-week duration. All subjects were required to give an informed consent before enrolling into the study.